The marketing strategy of grouper fish in increasing fishermen’s income in North Buton, Indonesia - Ittaqullah, Nurul (Priviet Social Sciences Journal, 2026)
This study examines how marketing strategy can enhance the income of small-scale grouper fishermen (Epinephelus spp.) in North Buton Regency, Southeast Sulawesi, Indonesia, where high market demand for premium marine products has not been matched by proportional income gains at the producer level. Despite the increasing domestic and export demand for grouper fish, fishermen in coastal regions remain constrained by traditional marketing channels, limited bargaining power, and rising operational costs. Using a descriptive mixed-methods approach, this study analyzes primary data collected from 15 purposively selected grouper fishermen in Kulisusu District, complemented by secondary data from official statistics and peer-reviewed literature. Fishermen’s income was assessed through cost–revenue analysis, and strategic priorities were formulated using an integrated SWOT framework, internal–External Factor Evaluation (IFE–EFE), and the Quantitative Strategic Planning Matrix (QSPM). The results show that the average net income of grouper fishermen is IDR 1,390,000 per month, indicating income vulnerability despite strong market demand. The SWOT and IE matrix results position the business in a “grow and build” quadrant, suggesting the feasibility of intensive strategies. QSPM analysis identified market penetration through increased catch efficiency while maintaining product freshness and quality as the most attractive strategy. This study contributes empirical evidence on small-scale fishery marketing strategies and provides practical insights for income improvement and sustainable coastal fishery development in eastern Indonesia.